Study Buckling Stability of High Pier Pile Foundation on A Steep Slope - Zhang, Chengli; Shen, Quan; Yan, Yuan (International Journal of Management and Education in Human Development, 2022)
At present, the research on the buckling stability of high pier usually regards the connection of pile and pier as fixed end and the top of pier as free or elastic hinge, which is difficult to fully and truly reflect the boundary conditions of pier, and does not consider the influence of the interaction between rock and soil and pile on the buckling stability of high pier. Based on the research background of practical engineering, ABAQUS finite element program is selected as the analysis tool, combined with the mechanical characteristics of high pier pile foundation in steep slope section, considering the pile-soil interaction, the linear buckling model is used to analyze the stability of steep slope pile foundation. By solving the model, the corresponding critical buckling load of bridge foundation pile in steep slope section is obtained. The rationality of this method can be seen by comparing the calculation results in this paper with those in the code. The results show that the critical buckling load PCR increases nonlinearly with the pile diameter, increases first and then decreases slowly with the increase of lateral force, and increases with the increase of slope angle. The research results can serve the design and construction of high pier pile foundation on steep slope.